2001
DOI: 10.1523/jneurosci.21-19-07506.2001
|View full text |Cite
|
Sign up to set email alerts
|

Synapse-Associated Protein 97 Selectively Associates with a Subset of AMPA Receptors Early in their Biosynthetic Pathway

Abstract: The regulation of AMPA receptors at the postsynaptic membrane is a fundamental component of synaptic plasticity. In the hippocampus, the induction of long-term potentiation increases the delivery of GluR1, a major AMPA receptor subunit in hippocampal pyramidal neurons, to the synaptic plasma membrane through a mechanism that requires the PDZ binding domain of GluR1. Synapse-associated protein 97 (SAP97), a member of the membrane-associated guanylate kinase family, is believed to associate with AMPA receptors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
222
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(251 citation statements)
references
References 47 publications
28
222
1
Order By: Relevance
“…As discussed above, the PDZ protein, SAP97, is implicated in the expression of AMPA receptor subunits as well as in the stabilization of the AMPA receptor complexes (Jourdi et al 2001;Sans et al 2001). In agreement, our preliminary study revealed that other AMPA receptor subunits, GluR2/3, were also decreased in the same prefrontal samples (58% reduction, U 25,14 ¼ 249, Z ¼ 2.16, p ¼ 0.03).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…As discussed above, the PDZ protein, SAP97, is implicated in the expression of AMPA receptor subunits as well as in the stabilization of the AMPA receptor complexes (Jourdi et al 2001;Sans et al 2001). In agreement, our preliminary study revealed that other AMPA receptor subunits, GluR2/3, were also decreased in the same prefrontal samples (58% reduction, U 25,14 ¼ 249, Z ¼ 2.16, p ¼ 0.03).…”
Section: Discussionsupporting
confidence: 84%
“…For example, Pick 1 and GRIP1, which both interact with the C-terminal terminal of the AMPA receptor subunits, GluR2/3, are involved in their internalization and synaptic stabilization (Dong et al 1999;Dev et al 1999;Chung et al 2000;Daw et al 2000;El-Husseini et al 2000;Osten et al 2000). SAP97 interacts with the AMPA receptor subunit GluR1 and stabilizes receptor protein expression at postsynaptic sites (Leonard et al 1998;Jourdi et al 2001;Sans et al 2001). Among the various PDZ proteins, levels of the PDZ protein SAP97 were specifically decreased in the prefrontal cortex of schizophrenics (59%, p < 0.05) compared to those in controls in the present experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three antibodies to mGluR5 were obtained from Chemicon International (Temecula, CA, USA); another from Chemicon was made to the last 13 amino acids and recognizes both mGluR5 and mGluR1alpha. Antibodies to AMPA receptors, NR1, NR2A/B, PSD-95, PSD-93, SAP97 and SAP102 were characterized in general and for immunogold labeling in hippocampus by our lab (Petralia and Wenthold, 1992;Petralia et al, 1994aPetralia et al, ,b, 1999Sans et al, 2000Sans et al, , 2001. Some new labeling studies were carried out for NR1 (amino acids 909-938; affinity-purified; recognizes the intracellular domain), SAP97 (amino acids 1-105; previous published studies used both this antiserum and an identical affinity-purified antibody), and SAP102 (amino acids 1-119; antiserum; previous published studies used an identical affinity-purified antibody).…”
Section: Antibodies and Their Characterizationmentioning
confidence: 99%
“…After chemiluminescence detection, films were scanned using a Molecular Dynamics densitometer. Subcellular fractionation of P2 rat brains was performed as described in Sans et al (2001). The synaptosome fraction, isolated by discontinuous sucrose gradient centrifugation, was solubilized in cold 0.5% Triton X-100 and centrifuged to obtain the PSD I pellet.…”
Section: Immunoblot Analysis and Subcellular Fractionationmentioning
confidence: 99%